2011
DOI: 10.1186/1471-2407-11-248
|View full text |Cite
|
Sign up to set email alerts
|

PI3K pathway activation results in low efficacy of both trastuzumab and lapatinib

Abstract: BackgroundHuman epidermal growth factor receptor 2 (HER2) is the most crucial ErbB receptor tyrosine kinase (RTK) family member in HER2-positive (refered to HER2-overexpressing) breast cancer which are dependent on or "addictive" to the Phosphatidylinositol-3-kinase (PI3K) pathway. HER2-related target drugs trastuzumab and lapatinib have been the foundation of treatment of HER2--positive breast cancer. This study was designed to explore the relationship between PI3K pathway activation and the sensitivity to la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(91 citation statements)
references
References 56 publications
5
83
1
2
Order By: Relevance
“…Compared with Caucasians, breast cancer in Oriental populations is a heterogeneous disease with divergent molecular mechanisms of pathogenesis. One study (Wang et al, 2011) also found a lower PIK3CA mutation rate (12.3%) in Chinese breast cancers. In addition, of the PIK3CA mutations detected in our study, 44.44% were E542K mutations, 33.33% were E545K, and 22.22% were H1047R; no mutations of other sites were found.…”
Section: Discussionmentioning
confidence: 90%
“…Compared with Caucasians, breast cancer in Oriental populations is a heterogeneous disease with divergent molecular mechanisms of pathogenesis. One study (Wang et al, 2011) also found a lower PIK3CA mutation rate (12.3%) in Chinese breast cancers. In addition, of the PIK3CA mutations detected in our study, 44.44% were E542K mutations, 33.33% were E545K, and 22.22% were H1047R; no mutations of other sites were found.…”
Section: Discussionmentioning
confidence: 90%
“…Loss of PTEN in BT474 cells by shRNAs was shown to lead to lapatinib resistance both in vitro and in vivo [25]. Similarly, activation of PI3K signaling resulting from PTEN loss or PI3K mutations has been reported for both trastuzumab and lapatinib resistance in patients [26]. On the other hand, the response to lapatinib of ErbB2-overexpressing PTEN-knockdown BT474 and AU565 cell lines, and of patients with inflammatory breast cancers is independent of PTEN status [27].…”
Section: Discussionmentioning
confidence: 95%
“…Genetic alterations in the PI3K pathway are also implicated in reduced response to lapatinib treatment. 10 Methylation changes in CpG islands (CGI) and CpG shores (low CpG density areas ~2 Kb close to CGI) affect gene expression. 11 In addition to such local changes, global hypomethylation and chromosomal instabilities have been found in cancers.…”
Section: Introductionmentioning
confidence: 99%